2021
DOI: 10.1063/5.0057415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of syringe pump fluctuations on cell-free layer in hydrodynamic separation microfluidic devices

Abstract: Syringe pumps are widely used biomedical equipment which offer low-cost solutions to drive and control flow through microfluidic chips. However, they have been shown to transmit mechanical oscillations resulting from their stepper motors, into the flow, perturbing device performance. In this work, unlike previous studies at lower flow rates, we have uncovered that the relative pressure fluctuation plateau from 5mL/h onwards to approximately 2% of the average pressure. Furthermore, we find that absolute pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The key conclusion from present extensive literature study are as follows: The present review article compares various hemodynamic blood plasma separation geometries, based on separation efficiency, SE and hematocrit, Hct, in three categories such as (1) highly diluted blood, i.e., Hct < 10%, (2) moderately diluted blood, i.e., 10 ≤ Hct ≤ 37 (3) whole blood, i.e., Hct ≥ 37%. From the comparative study, it can be concluded that obtaining both high SE and yield, simultaneously is very challenging as it requires a precise control over flow instabilities (i.e., high-pressure fluctuation), flow rate, specific channel dimensions, etc., (Haque et al 2020 , 2021 ). Certain limitations have been noted for channel-based separation devices, in terms of their application in niche areas as in clinical field, biological field, etc., which requires the devices to separate blood with high purity, high yield, and biological validation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The key conclusion from present extensive literature study are as follows: The present review article compares various hemodynamic blood plasma separation geometries, based on separation efficiency, SE and hematocrit, Hct, in three categories such as (1) highly diluted blood, i.e., Hct < 10%, (2) moderately diluted blood, i.e., 10 ≤ Hct ≤ 37 (3) whole blood, i.e., Hct ≥ 37%. From the comparative study, it can be concluded that obtaining both high SE and yield, simultaneously is very challenging as it requires a precise control over flow instabilities (i.e., high-pressure fluctuation), flow rate, specific channel dimensions, etc., (Haque et al 2020 , 2021 ). Certain limitations have been noted for channel-based separation devices, in terms of their application in niche areas as in clinical field, biological field, etc., which requires the devices to separate blood with high purity, high yield, and biological validation.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, there is always a limitation of the blood plasma separating devices in terms of hemolysis, extraction time, etc. These limitations can be overcome with a specific choice of channel dimensions, inlet flow rate, reduction in the flow fluctuations, etc., which can lead to a higher separation efficiency with high cell viability, but for a limited hematocrit (Lee et al 2011 ; Haque et al 2020 , 2021 ).…”
Section: Plasma Separation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main barrier in the microfluidic approach is the cell-cell interaction between red blood cells. When high volume fractional blood is flowed at a high flow rate, the cell interaction between a large number of RBCs in the microfluidic channel increases, which inhibits the cell-free layer formation and other deterministic effects, thus reducing the separation performance [50]. As a result, the use of high-volume fractional blood in the above comparative high-throughput studies has resulted in much lower separation yields.…”
Section: Plos Onementioning
confidence: 99%
“…RBC aggregation affects the bluntness and skewness of the velocity profiles, and impacts on the properties of the cell depleted layer (CDL), which forms adjacent to the channel walls. Recent studies have shown that the CDL is also affected by the design of the utilised syringe pumps 35 . The strong relationship between aggregate size, shear rate and viscosity in aggregated blood microchannel flows has also been illustrated in other works [36][37][38] .…”
mentioning
confidence: 99%